2014
DOI: 10.18410/jebmh/2014/209
|View full text |Cite
|
Sign up to set email alerts
|

Road Safety; How Well - Informed Are Our Rural Population?

Abstract: A community based cross sectional study was carried out in a rural block of north Tamilnadu to assess the knowledge; attitude and practice of general population of age group 18 to 35 regarding road safety rules. A semi structured interviewed administered questionnaire was administered among a 115 participants. 82.1% drove vehicle without a license. 75.7% did not know the side of the road to be used by pedestrians for walking. Only 15.7% could recognize all 5 traffic signals properly. Nearly 95.7% agree that he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…In contrast the study carried out among the rural population in Vellore, had a higher proportion of male participants (66.1%). 11,12 In the present study 62.4% of the participants had 10 or less years of schooling as compared to 45.2% of the population in the study done in Vellore. 11 While nearly 83% of the participants in the Vellore study reported to know driving, only 39.2% of the participants in this study stated the same.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…In contrast the study carried out among the rural population in Vellore, had a higher proportion of male participants (66.1%). 11,12 In the present study 62.4% of the participants had 10 or less years of schooling as compared to 45.2% of the population in the study done in Vellore. 11 While nearly 83% of the participants in the Vellore study reported to know driving, only 39.2% of the participants in this study stated the same.…”
Section: Discussionmentioning
confidence: 45%
“…11,12 In the present study 62.4% of the participants had 10 or less years of schooling as compared to 45.2% of the population in the study done in Vellore. 11 While nearly 83% of the participants in the Vellore study reported to know driving, only 39.2% of the participants in this study stated the same. These differences could be because of the higher proportion of female participants and a higher age bracket as compared to the Vellore study population.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations